Learning to Write Descriptive Texts Based on Batik Culture of BIPA Students at the Indonesian Embassy in London - Yulianeta Yulianeta; Dewi Prajnaparamita Amandangi (Master Program in Linguistics, Diponegoro University, 2021)
Learning Indonesian as a Foreign Fuller (BIPA) is carried out along with the introduction of culture to learners. Apart from language learning, the introduction of culture can also provide a more concrete picture of Indonesian identity. This article focuses on the study of writing skills, in particular, on writing descriptive texts. The learning to write based on Indonesian culture, especially batik culture. Using qualitative methods, this research was conducted for approximately three months in the period of September-December 2019. The data of this study were the ability to write descriptive texts of BIPA students at the Indonesian Embassy in London. The research subjects were 9 BIPA students at the Indonesian Embassy in London. The results of this study are descriptions of the learning to write descriptive texts of BIPA students and descriptions of culture-based learning of BIPA students at the Indonesian Embassy in London. The descriptive text is used as an alternative approach in learning to write for BIPA because it makes it easier for the students to learn vocabulary as well as culture.